Time-resolved transmission spectroscopy of the ultra-hot Jupiter WASP-189 b - Prinoth, Bibiana; Hoeijmakers, H. J.; Pelletier, S.; Kitzmann, D.; Morris, B. M.; Seifahrt, A.; Kasper, D.; Korhonen, H. H.; Burheim, M.; Bean, J. L.; Benneke, B.; Borsato, N. W.; et al. (Astronomy and astrophysics, 2023)
Ultra-hot Jupiters are tidally locked with their host stars, dividing their atmospheres into a hot dayside and a colder nightside. As the planet moves through transit, different regions of the atmosphere rotate into view, revealing different chemical regimes. Highresolution spectrographs can observe asymmetries and velocity shifts and offer the possibility for time-resolved spectroscopy. The ultra-hot Jupiter WASP-189 b has recently been found to possess a rich transmission spectrum with evidence for atmospheric dynamics and chemical inhomogeneity. In this study, we search for other atoms and molecules in the planet’s transmission spectrum and investigate asymmetric signals. We analysed and combined eight transits of the ultra-hot Jupiter WASP-189 b collected with the HARPS, HARPS-N, ESPRESSO, and MAROON-X high-resolution spectrographs. Using the cross-correlation technique, we searched for neutral and ionised atoms as well as oxides, and we compared the obtained signals to model predictions. We report significant detections for H, Na, Mg, Ca, Ca+, Ti, Ti+, TiO, V, Cr, Mn, Fe, Fe+, Ni, Sr, Sr+, and Ba+. Of these, Sr, Sr+, and Ba+ are detected for the first time in the transmission spectrum of WASP-189 b. In addition, we robustly confirm the detection of titanium oxide based on observations with HARPS and HARPS-N using the follow-up observations performed with MAROON-X and ESPRESSO. By fitting the orbital traces of the detected species by means of time-resolved spectroscopy using a Bayesian framework, we inferred posterior distributions for orbital parameters as well as line shapes. Our results indicate that different species must originate from different regions of the atmosphere to be able to explain the observed time dependence of the signals. Throughout the course of the transit, most signal strengths are expected to increase due to the larger atmospheric scale height at the hotter trailing terminator. For some species, however, we instead observed that the signals weaken, either due to the ionisation of atoms and their ions or the dissociation of molecules on the dayside.
Gesehen am 23.09.2024